Phthalocyanines : photochemical, electrochemical and biomimetic catalytic behaviour - Sehlotho, Nthapo (Rhodes University, Faculty of Science, Department of Chemistry, 2007)
This thesis explored use of metallophthalocyanines as electrocatalysts towards thiol and thiocyanate oxidation, nitrosothiol decomposition and reduction of oxygen, as well as biomimetic and photo-catalysts of cyclohexene oxidation. 2-mercaptoethanol (2-ME), L-cysteine (CYS) and reduced glutathione (GSH) thiols were oxidized on cobalt tetra ethoxythiophene and cobalt tetra phenoxy pyrrole phthalocyanine modified glassy carbon electrodes, whose catalytic activity was found to depend on pH, film thickness and method of electrode modification. Oxidation of thiocyanate (SCN-), CYS and 2-ME was catalyzed by a selfassembled monolayer of cobalt tetraethoxythiophene Thiocyanate oxidation occurred via two electron transfer, whereas that of CYS and 2-ME required 1 electron. The oxidations of SCN- and 2-ME were catalyzed by ring based processes, while CYS was catalyzed by both Co[superscript III]/Co[superscript II] process and ring-based processes. Oxidation of GSH and 2-ME was conducted on screen printed graphite electrodes modified with cobalt phthalocyanine. Activity depended on method of electrode modification and CoPc % composition. Decomposition of Snitrosoglutathione occurred in the presence of copper ions and NaBH[subscript 4]. Reduced and oxidized glutathione were detected as products using cobalt phthalocyanine adsorbed on an ordinary pyrolytic graphite electrode. Reduction of oxygen was electro-catalyzed by adsorbed manganese phthalocyanine complexes on glassy carbon electrodes. FePc, FePc(Cl)[subscript 16], CoPc and CoPc substituted with phenoxypyrrole and ethoxythiophene ligands were also used as electro-catalysts. Oxygen reduction occurred via two electron transfer in acidic and neutral media forming hydrogen peroxide, while water was formed in basic media via four electron transfer. Cyclohexene oxidation using tert-butylhydroperoxide or chloroperoxy benzoic acid as oxidants in the presence of FePc, FePc(Cl)[subscript 16] and CoPc formed cyclohexene oxide, 2-cyclohexen-1-ol, 2- cyclohexen-1-one and adipic acid. Product selectivity depended on the nature of catalyst and oxidant. The FePc(Cl)[subscript 16] catalyst was transformed into a Âµ-oxo dimer during the oxidation process while M[superscript III]Pc intermediates were formed with Co[superscript II]Pc and Fe[superscript II]Pc catalysts. Cyclohexene photooxidation catalyzed by zinc phthalocyanine using either red or white light formed 2-cyclohexen-1-one, 2-cyclohexen-1-ol, transcyclohexane diol, cyclohexene oxide and cyclohexene hydroperoxide via singlet oxygen and radical mechanisms. Product yields depended on the light wavelength and intensity, solvent, irradiation time and the rate of photodegradation of the catalyst.
Keywords: Phthalocyanines; Photochemistry; Electrochemistry; Biomimetics; Oxidation